2010
DOI: 10.1186/1476-4598-9-108
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-101 negatively regulates Ezh2 and its expression is modulated by androgen receptor and HIF-1α/HIF-1β

Abstract: BackgroundIn prostate cancer (PCa), the common treatment involving androgen ablation alleviates the disease temporarily, but results in the recurrence of highly aggressive and androgen-independent metastatic cancer. Therefore, more effective therapeutic approaches are needed. It is known that aberrant epigenetics contributes to prostate malignancy. Unlike genetic changes, these epigenetic alterations are reversible, which makes them attractive targets in PCa therapy to impede cancer progression. As a histone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
189
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(201 citation statements)
references
References 55 publications
(80 reference statements)
9
189
2
1
Order By: Relevance
“…By analyzing the 3'-UTR sequence of EZH2, it has recently been shown that there are two predicted miR-101 target sites and one predicted miR-26a target site in the 3'-UTR of EZH2. 46 We performed a similar analysis and found that there was also a potential target site for miR-128a near one of the miR-101 target sites (Online Supplementary Figure S6). miR-26a was not decreased in ATL cells, and there was no correlation between miR-26a expression and EZH2 expression or miR-128a expression and BMI1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the 3'-UTR sequence of EZH2, it has recently been shown that there are two predicted miR-101 target sites and one predicted miR-26a target site in the 3'-UTR of EZH2. 46 We performed a similar analysis and found that there was also a potential target site for miR-128a near one of the miR-101 target sites (Online Supplementary Figure S6). miR-26a was not decreased in ATL cells, and there was no correlation between miR-26a expression and EZH2 expression or miR-128a expression and BMI1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of several androgen-inducible miRNA (miR-21, miR-101, miR-125b, miR-221 and miR-222) have been well-characterized in prostate cancer cells, and these miRNA have been found to be involved in the progression to androgen independence. [148][149][150][151][152] MiR-21 has an androgen-responsive element, and is directly upregulated by androgens in prostate cancer cell lines. In addition, miR-21 was expressed at higher levels in AR-positive than in AR-negative prostate cancer cells.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%
“…In both solid tumors and hematopoietic malignancies, more aggressive subtypes were associated with overexpression of EZH2 caused by different mechanisms, including genomic loss of the miR-101 locus (39)(40)(41). Relevant to the latter observation, induced expression of miR-101 in cancer cell lines inhibits the expression and function of EZH2 (42).…”
Section: Mir-101 Modulates the Expression Of The Ezh2 Methyltransferamentioning
confidence: 99%